Forms of faith : literary form and religious conflict in early modern England - Baldo, Jonathan; Karremann, Isabel (Manchester Religious Studies, 2017)
This collection of essays opens a new perspective on the interplay of religious conflict and literary culture in early modern England. Placing the focus on negotiation instead of escalation, thirteen distinguished international scholars explore the specific ways available to mediate, displace or suspend confessional conflict in and through literature.